Study protocol for a prospective, non-controlled, multicentre clinical study to evaluate the diagnostic accuracy of a stepwise two-photon excited melanin fluorescence in pigmented lesions suspicious for melanoma (FLIMMA study). Issue 12 (19th December 2016) - Fink, Christine; Hofmann, Maja; Jagoda, Agata; Spaenkuch, Iris; Forschner, Andrea; Tampouri, Ioanna; Lomberg, Diana; Leupold, Dieter; Garbe, Claus; Haenssle, Holger A
Abstract : Introduction: Non-invasive, nanosecond, stepwise two-photon laser excitation of skin tissue was shown to induce melanin fluorescence spectra that allow for the differentiation of melanocytic nevi from cutaneous melanoma. Methods and analysis: This prospective, non-controlled, multicentre clinical study is performed to evaluate the diagnostic performance of the stepwise two-photon excited melanin fluorescence in the detection of cutaneous melanoma. The comparator will be the histopathological diagnosis. A total of 620 pigmented skin lesions suspicious for melanoma and intended for excision will be enrolled. Ethics and dissemination: Ethics approval was provided by the local ethics committees of the medical faculties of the University of Tuebingen, Heidelberg and Berlin. Study registration: The FLIMMA study NCT02425475 .